Use of acoustic methods for the protection of harbour porpoises (Phocoena phocoena) in German Waters - Dähne, Michael (2014)
Harbour porpoises Phocoena phocoena in German waters are faced with a variety of different anthropogenic and natural stressors that can have serious effects on population development. Anthropogenic stressors include prey depletion, influences of chemical and pharmaceutical toxins, by-catch in static fishing gear, noise pollution and habitat degradation. Climate influences add to these stressors and may pose both natural as well as anthropogenic threats. Pile-driving noise for construction of offshore wind farms is a new influence that is suspected to have adverse effects on porpoises. Within German waters three subpopulations of porpoises can be found. The North Sea subpopulation extends into the Skagerrak and parts of the Kattegat, the Belt Sea subpopulations reaches from these regions into the waters of the Kiel and Mecklenburg Bight while the Baltic Proper subpopulation has its presumed boundaries at the Darß and Limhamn Sills and populates the waters of the inner Baltic Sea. While the abundance of porpoises in the North Sea seems stable, this has been questioned for the Belt Sea subpopulation. The Baltic Proper subpopulation is recognized as ‘critically endangered’ by the IUCN (International Union for Conservation of Nature) red list and surveys within the last decades have not lead to conclusive abundance estimates due to the scarcity of sightings. Within this study Stationary Acoustic Monitoring (SAM) with echolocation click loggers (T-PODs – Timing Porpoise Detectors and C-PODs – Cetacean PODs, both Chelonia Ltd., UK) was used to describe distribution patterns of porpoises and analyse factors driving acoustic presence of porpoises in German waters. Harbour porpoises use echolocation almost constantly and hence registrations on the loggers represent a relative measure for porpoise presence in an area. This relatively new method is still developing rapidly and neither analysis strategies nor devices are standardized as has been done for other assessment methods. However, when using these devices for ...